Question: For $n\ge 3$ determine all real solutions of the system of $n$ equations: $$x_1+x_2+\cdots+x_{n-1}=\frac{1}{x_n}\\ \cdots \\ x_1+x_2+\cdots+x_{i-1}+x_{i+1}+\cdots+x_n=\frac{1}{x_i}\\ \cdots \\ x_2+\cdots+x_{n-1}+x_n=\frac{1}{x_1}.$$

My approach: It is given that $$x_1+x_2+\cdots+x_{n-1}=\frac{1}{x_n}\\ \cdots \\ x_1+x_2+\cdots+x_{i-1}+x_{i+1}+\cdots+x_n=\frac{1}{x_i}\\ \cdots \\ x_2+\cdots+x_{n-1}+x_n=\frac{1}{x_1}.$$

Define $$S_n:=x_1+x_2+\cdots+x_n.$$

This implies that $$x_1+x_2+\cdots+x_{n-1}+x_n=x_n+\frac{1}{x_n}\\ \cdots \\ x_1+x_2+\cdots+x_{i-1}++x_i+x_{i+1}+\cdots+x_n=x_i+\frac{1}{x_i}\\ \cdots \\ x_1+x_2+\cdots+x_{n-1}+x_n=x_1+\frac{1}{x_1}.$$

Therefore, we have $$x_j+\frac{1}{x_j}=S_n, \forall 1\le j\le n.$$

Now for any $1\le j\le n,$ we have $$x_j+\frac{1}{x_j}=x_n+\frac{1}{x_n}\\ \implies \frac{1}{x_j}-\frac{1}{x_n}=x_n-x_j\\ \implies \frac{x_n-x_j}{x_nx_j}=x_n-x_j\\ \implies (x_n-x_j)\left(\frac{1}{x_nx_j}-1\right)=0\\ \implies x_j=x_n \text{ or } x_j=\frac{1}{x_n}.$$

Now let us have $i (0\le i\le n-1)$ of the $(n-1)$ numbers $x_j, 1\le j\le n-1$ such that $$x_j=x_n$$ and the rest $(n-1-i)$ numbers such that $$x_j=\frac{1}{x_n}.$$

Therefore, since $$x_1+x_2+\cdots+x_{n-1}=\frac{1}{x_n}\\\implies i.x_n+(n-1-i).\frac{1}{x_n}=\frac{1}{x_n}\\ \implies i.x_n^2+(n-2-i)=0\\\implies i.x_n^2=2+i-n.$$

Now since $x_n\in\mathbb{R}$ and $x_n\neq 0\implies x_n^2>0.$ Now since $i\ge 0\implies i.x_n^2\ge 0 \implies 2+i-n\ge 0\implies i\ge n-2.$ Therefore $i=n-2,n-1$.

Now when $i=n-2$, we have $(n-2)x_n^2=0.$ Now since it is given that $n\ge 3\implies n-2\ge 1>0$. Therefore $x_n^2=0\implies x_n=0$. But $x_n\neq 0$. Therefore $i\neq n-2$.

Now when $i=n-1$, we have $(n-1)x_n^2=1\implies x_n^2=\frac{1}{n-1}\implies x_n=\pm\frac{1}{\sqrt{n-1}}.$ Therefore we have $$x_1=x_2=\cdots=x_n=\pm\frac{1}{\sqrt{n-1}}.$$

Therefore the required set of solutions are $$(x_1,x_2,\cdots,x_n)=\left(\frac{1}{\sqrt{n-1}},\frac{1}{\sqrt{n-1}},\cdots,\frac{1}{\sqrt{n-1}}\right),\left(-\frac{1}{\sqrt{n-1}},-\frac{1}{\sqrt{n-1}},\cdots,-\frac{1}{\sqrt{n-1}}\right).$$

Can someone check if my solution is correct or not? And if correct, is there a more better and efficient solution than this?


I get the same result. Here's my work.

I abhore "..."s, so I'll write the equations like this:

For $i=1$ to $n$,

$\sum_{k=1, k\ne i}^n x_k =\dfrac1{x_i} $.

Filling in the missing term,

$\sum_{k=1}^n x_k =\dfrac1{x_i}+x_i $.

Letting $S = \sum_{k=1}^n x_k$, we have $S = \dfrac1{x_i}+x_i $ so $x_i^2-Sx_i+1 = 0$ or $x_i = \dfrac{S\pm\sqrt{S^2-4}}{2} $.

Also, for $i \ne j$, $\dfrac1{x_i}+x_i = \dfrac1{x_j}+x_j $ or, multiplying by $x_ix_j$, $x_j-x_i^2x_j =x_i-x_ix_j^2 $ or $x_i-x_j =x_ix_j^2-x_i^2x_j =x_ix_j(x_j-x_i) $.

If $x_i \ne x_j$ then $x_ix_j = -1$ so $x_j = -\dfrac1{x_i} $.

Set $i = n$ so the other values are either $x_n$ or $-\dfrac1{x_n} $.

Suppose $m$ of them are $x_n$. Then $S =mx_n-(n-m)\dfrac1{x_n} $ so $x_n+\dfrac1{x_n} =mx_n-(n-m)\dfrac1{x_n} $ or, writing $x$ for $x_n$, $(m-1)x=(n-m+1)\dfrac1{x} $.

We can't have $m=1$ for then $\dfrac1{x} = 0$.

Therefore $m \ge 2$ so that $(m-1)x^2=(n-m+1) $ or $x =\pm\sqrt{\dfrac{n-m+1}{m-1}} $.

I will choose $x =\sqrt{\dfrac{n-m+1}{m-1}} $ for now.


$\begin{array}\\ S &=m\sqrt{\dfrac{n-m+1}{m-1}}-(m-n)\sqrt{\dfrac{m-1}{n-m+1}}\\ &=x+\dfrac1{x}\\ &=\sqrt{\dfrac{n-m+1}{m-1}}+\sqrt{\dfrac{m-1}{n-m+1}}\\ \end{array} $

so, multiplying by $\sqrt{(n-m+1)(m-1)} $,

$m(n-m+1)-(m-n)(m-1) =(n-m+1)+(m-1) $ or $n =mn-m^2+m-(m^2-(n+1)m+n) =2m(n+1)-2m^2-n $ or $0 =2(m(n+1)-m^2-n) $ or $0 = m^2-(n+1)m+n $ or $0 =(m-1)(m-n) $.

Since $m > 1$, we have $m = n$ so all the $x_i$ are the same, so $S = \dfrac{n}{\sqrt{n-1}} $ and each $x_i =\dfrac1{\sqrt{n-1}} $.

Note that $\dfrac1{\sqrt{n-1}} +\sqrt{n-1} =\dfrac{1+n-1}{\sqrt{n-1}} =\dfrac{n}{\sqrt{n-1}} = S $.

If $x =-\sqrt{\dfrac{n-m+1}{m-1}} $ then all the signs are reversed, so the final result is the same.


We have $$x_1+x_2+\cdots+x_{n-1}-\frac{1}{x_n}=0\\x_1+x_2+\cdots-\frac{1}{x_{n-1}}+x_n=0\\.........................\\.........................\\-\frac{1}{x_1}+x_2+\cdots+x_{n-1}+x_n=0 $$ It follows $$\sum_{i=1}^{i=n}\left((n-1)x_i-\frac{1}{x_i}\right)=\sum_{i=1}^{i=n}\frac{(n-1)x_i^2-1}{x_i}=0 $$ Then a clear solution is given by $(n-1)x_i^2-1=0$ for all $i$.

Thus the two solutions given by the O.P.

  • $\begingroup$ Now you need to show that these are the only solutions. $\endgroup$ – marty cohen Apr 4 '20 at 4:42
  • $\begingroup$ I just want to show the two solutions of the O.P. (I was aware of what you say, even if you don't believe me). Regards. $\endgroup$ – Piquito Apr 4 '20 at 13:20

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.